Conjugation of milk proteins and reducing sugars and its potential application in the improvement of the heat stability of (recombined) evaporated milk. (February 2021) - Wu, Jianfeng; Li, Hao; A'yun, Qurrotul; Sedaghat Doost, Ali; De Meulenaer, Bruno; Van der Meeren, Paul
Abstract: Background: Milk proteins, i.e. caseins and whey proteins, are widely used in many fields due to their various nutritional and functional properties. In manufacturing some milk protein-containing products, in particular with a high concentration of milk proteins, such as (recombined) evaporated milk, one of the biggest challenges is the possible heat-induced coagulation due to the denaturation of milk proteins, particularly the whey proteins, and their interactions during the intense sterilization operation that is typically used to ensure a long shelf-life for these products. As this phenomenon highly influences the product quality and production equipment, it is of great importance to improve the heat stability of the milk proteins. Scope and approach: Conjugation between milk proteins and reducing sugars has been shown to substantially modify the techno-functional properties of milk proteins including their heat stability. This review gives emphasis on the improved heat stability of conjugates of milk proteins and reducing sugars. The conjugation of milk proteins and reducing sugars as a potential strategy to overcome the heat instability of milk proteins in a context of commercial dairy products is also discussed. Key findings and conclusions: This strategy has been found to be effective to enhance the heat stability of milk proteins, and some research has given focus on its application in the commercial dairy products. However, further research is needed in the future. Highlights: The heat stability of REM is improved by the milk protein-reducing sugar conjugation. The approaches to achieve the desirable conjugation are reviewed. Compared with polysaccharides, the required time is generally shorter. No additional ingredient and pre-treatment are required in the case of lactose.